Evaluasi Pembinaan Prestasi pada Olahraga Prestasi Koni Kabupaten Dompu - Iman Zulfikar; Taufik Hidayat; Sandi Achmat Pratama; Ervin Oktavianis (Jurnal Syntax Admiration, 2024)
The purpose of this research to evaluate on the construction of achievement coaching on KONI sport performance in Dompu Regency. This research is an evaluation study using a qualitative method, with an approach using the CIPP (Context, Input, Process, Product) evaluation model. The research subjects consisted of KONI, coaches, athletes, parents, and sport managers. The study's findings demonstrated that the level of accomplishment in terms of context-related factors for KONI's athletic performance development in the Dompu Regency falls into the category of rather good. From an input perspective, the category as a whole is sufficiently good. The category's process is deemed to be fairly good. Regarding the item in the wide range inside the favorable classification, where the performance in the regional and national competition, specifically PORPROV NTB 2023, has improved from the third place on PORPROW 2018 to the second place on PORPROV 2023. Additionally, the number of athletes from Dompu Regency has increased in PON Aceh 2024.